Inside a Postpartum Nursing Center: Tradition and Change - Yueh-Chen Yeh, RN, MSN, PhD; Winsome St John, RN, RM, PhD; Lorraine Venturato, RN, RM, PhD (Elsevier, 2016)
Purpose: The purpose of this study was to explore how traditional ritual practices are incorporated into the context of contemporary healthcare. Methods: An ethnographic study was conducted, using observations and interviews with 27 first-time mothers and 3 nurses at a postpartum nursing center in Taipei, Taiwan. Results: Nursing routines, policies and care provision at the center affected the way traditional ritual practices were conducted. New mothers in this study constructed their everyday activities at the center by incorporating and modifying the ritual practices inside and outside the postpartum nursing center setting. Conclusions: Social changes have an influence on traditional postpartum ritual practices so a postpartum nursing center becomes a choice for postpartum women. Thus, health care professionals should value their own functions and roles at the postpartum nursing center since the new mothers regard them as the primary support resource to help them recover from giving birth. Therefore, they need to re-examine their practices from the postpartum women's perspective to provide better support and sensitive care to postpartum women and their families.